Analisis Faktor yang Memengaruhi Kepatuhan Penggunaan Antibiotik pada Pasien Poli Gigi di Pukesmas Bakunase - Cantika Saudila; Magdarita Riwu; Matias N. Kolobani (LPPM Universitas Abdurrab, 2026)
Non-compliance with antibiotic use is a key factor triggering therapeutic failure and increasing risk of antibiotic resistance. Various factors are suspected to influence patient compliance, including sociodemographics, knowledge, understanding of usage instructions, and patient perceptions toward antibiotics. This study aims to analyze factors influencing compliance with antibiotic use among dental clinic patients at Bakunase Public Health Center, Kupang City. This is an analytical observational study with a cross-sectional design. Sampling technique used consecutive sampling with a total of 50 respondents. Data were obtained through questionnaires and medical records, then analyzed using univariate analysis, chi-square test for bivariate analysis, and logistic regression for multivariate analysis. Results showed that respondent characteristics were dominated by 18-40 age group (48%), females (60%), secondary education level (50%), and those unemployed/having no income (58%). A total of 52% of respondents were classified as non-compliant. Analysis indicated that sociodemographic factors and perceptions had no significant effect on compliance (p > 0.05). Conversely, level of knowledge and understanding of instructions were most influential factors on antibiotic compliance (p = 0.017; OR = 5.069; 95% CI = 1.341-19.160), with understanding of instructions being the most dominant factor. Therefore, improving quality of education and counseling by healthcare professionals regarding proper antibiotic use is highly necessary to enhance patient compliance.